An Evaluation Approach for Physical Education Teaching Practice Quality Using Stochastic Simulation Algorithm - Zhou, Changlei; Ma, Tingting (Mobile information systems, 2022)
In order to increase the precision of the quality assessment of institution physical education, as well as teaching practice, the assessment system of institution physical education, as well as teaching practice quality, based on stochastic simulation algorithm, is put forward. Then, we construct the constraint parameter model of institution physical education, as well as teaching practice quality assessment, and analyze the hierarchical structure characteristics of institution physical education, as well as teaching practice quality. Subsequently we standardize the data fusion through the developmental characteristic analysis approach of teaching quality assessment and analyze the confidence level of institution physical education, as well as teaching practice quality, in order to construct frequent item set parameters. Moreover, we adopted the combination analysis approach of support and confidence level to analyze the correlation pattern and identify the characteristics, so as to recognize the characteristic analysis of institution physical education, as well as teaching practice quality level. The random simulation and association rule decision-making approaches are implemented to assess the quality level of institution physical education, as well as teaching practice, and the random simulation dynamic detection and the maximum matching degree analysis approach are implemented to assess the quality level of institution physical education, as well as teaching practice. The simulation outcomes confirm that the precision of this approach in evaluating the quality of institution physical education, as well as teaching practice, is considerably high, and the quality level of institution physical education, as well as teaching practice, is significantly increased.